Analsis Faktor-faktor yang Berhubungan dengan kejadian Stunting di Pinggiran Sungai Wilayah Kerja Puskesmas Alalak Selatan Kota Banjarmasin - Netty Netty Netty; Husnul Khatimatun I; Ari Widyarni (HB PRESS, 2020)
Stunting is a chronic nutritional problem among under-five children, characterized by a shorter height than children at their age. Stunted children can occur due to nutritional disorders in the first 1,00 days of life, and it is influenced by many factors (e.g., mothers’ nutritional status during pregnancy and feeding behavior). Behavior is affected by mothers’ education and knowledge. The prevalence of moderately and severely stunted under-five children was 30.08% in Indonesia, 33.08% in South Kalimantan, and 28.75% in Banjarmasin City (Riskesdas, 2018). Puskesmas Alalak Selatan is in charge of 3 Kelurahan (Pangeran, Alalak Selatan, and Kuin Utara). Objective: To determine factors related to the incidence of stunting among under-five children on the riverbank in the work area of Puskesmas Alalak Selatan. This was an analytical study using a case-control study design. The data analysis used computer programs and the chi-square test with a 95% confidence level. The population was mothers with under-five children aged 12-59 months with a total sample of 60 people (30 mothers with stunted children as cases and 30 mothers with normal children as the control). Results: 50% of stunted under-five children (cases) and 50% of normal under-five children (control). Thirty-eight people (63.3%) had high education, and three people (5.0%) had low education. Twenty-five people (41.7%) had good knowledge, and 20 people had low knowledge (33.3%). Twenty-nine mothers had CED (48.3%) and 31 mothers without CED (51.7%) during pregnancy. Mothers’ education, knowledge, and nutritional status during pregnancy were related to the incidence of stunting among under-five children on the riverbank in the work area of Puskesmas Alalak Selatan Banjarmasin City.